Continuity of cancer care: Where do Primary Care Practitioners fit in? - Jiwa, Moyez; McManus, Alexandra; Dadich, A. (Australian Cancer Society, 2013)
Cancer is the leading cause of illness in Australia and is a national health priority. Primary care in Australia is well positioned to support individuals diagnosed with cancer and their family/caretakers. However, obstacles exist that impact on the quality and continuity of care that primary care providers and community health professionals can provide. A rapid review of the research available revealed that the knowledge, attitudes and beliefs held by health professionals and patients can impact engagement in early detection, treatment and follow-up care. Health professionals have limited knowledge of evidence-based practices while cancer literacy among minority groups, including Aboriginal Australians, is lower than the population overall. In this paper, we provide a summary of the rapid review of the literature and provide some recommendations based on our research.